Cyberaddiction as a factor of formation of deviant behavior in adolescents with signs of personality accentuation - Tatarenko Олена (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to cyberaddiction as a factor of formation of deviant behavior in adolescents with signs of personality accentuation.